STM32-based Plant growth factor wireless remote monitoring system - CHAI ZONGQIAN; WU YANSHENG; WANG DONGFANG; LIANG SHILI; WANG SHUANGWEI; CAO CHUNLEI (2017)
The invention belongs to the application technology of agricultural science, and discloses a STM32-based Plant growth factor wireless remote monitoring system. The wireless remote monitoring system includes two parts, wherein the one part is a collection and sending part while the other part is receiving and displaying part. The hardware system is composed of a data information collecting terminal of a plant growth factor, a data information display terminal of the plant growth factor and a power supply system. The power supply system is supplied by USB wire, and can be provided by a mobile USB charging plug or a mobile power source; the software system is composed of data collection terminal software design and data display terminal software design. The wireless remote monitoring system is minimized and portable; data can be transmitted by the wireless transmission system; the measuring factors including soil humidity, air humidity, air temperature and lighting intensity, and precision are high, and the test